Proteins binding to 5' untranslated region sites: a general mechanism for translational regulation of mRNAs in human and yeast cells. - Stripecke, R (1994)
We demonstrate that a bacteriophage protein and a spliceosomal protein can be converted into eukaryotic translational repressor proteins. mRNAs with binding sites for the bacteriophage MS2 coat protein or the spliceosomal human U1A protein were expressed in human HeLa cells and yeast. The presence of the appropriate binding protein resulted in specific, dose-dependent translational repression when the binding sites were located in the 5' untranslated region (UTR) of the reporter mRNAs. Neither mRNA export from the nucleus to the cytoplasm nor mRNA stability was demonstrably affected by the binding proteins. The data thus reveal a general mechanism for translational regulation: formation of mRNA-protein complexes in the 5' UTR controls translation initiation by steric blockage of a sensitive step in the initiation pathway. Moreover, the findings establish the basis for novel strategies to study RNA-protein interactions in vivo and to clone RNA-binding proteins.